Identifying the therapeutic potential of novel compounds in the treatment of Glioblastoma Multiforme - Keenan, Emily (Trinity College Dublin. School of Medicine. Discipline of Physiology, 2023)
Glioblastoma multiforme (GBM) is the most common and aggressive brain cancer in adults with a dismal 5-year survival rate of <5%. Despite advanced diagnostic and multimodal treatments including surgery, followed by radiotherapy and chemotherapy (CRT), treatment resistance is a major clinical challenge and the survival rates for GBM are not improving. Therefore, innovative therapeutic approaches are urgently needed for GBM patients. (E)-2-(2-(Pyrazin-2-yl)vinyl)phenol, Pyrazinib (P3) a small molecule pyrazine compound has shown significant therapeutic potential as a radiosensitiser in oesophageal cancer and here we assess its therapeutic potential in GBM. (E)-2-(2-quinolin-2-yl-vinyl)-benzene-1,4-diol HCl, 1,4 dihydroxy quininib (Q8), an antagonist of the cysteinyl leukotriene receptor-1 has shown potential as novel anti-angiogenic in colorectal cancer models and here we assess its therapeutic utility in GBM. Natural killer (NK) cells are potent anti-tumour immune cells and are gaining momentum as cell-based immunotherapies. This study investigates Pyrazinib (P3), 1,4 dihydroxy quininib (Q8) and a P3 prodrug called P3 Phosphate for their potential to sensitise GBM tumours to current standard-of-care chemotherapy and for their utility in combination with NK cell therapies.
APPROVED